Journal of Social Policy (Cambridge)
The Journal of Social Policy carries high quality articles on all aspects of social policy in an international context. It places particular emphasis upon articles which seek to contribute to debates on the future direction of social policy, to present new empirical data, to advance theories, or to analyse issues in the making and implementation of social policies. The Journal of Social Policy is part of the 'Social Policy Package', with Social Policy and Society
Keywords: Sociology